THE EFFECTIVENESS OF INFORMATION GAP ACTIVITY TO IMPROVE STUDENTS’ SPEAKING ABILITY - Koyongian, Dominique; Salam, Uray; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focused on increasing students’ speaking ability by using Information Gap Activity. This research was conducted to the eleventh grade students of SMA Santo Paulus Pontianak in Academic Year 2013/2014. The purpose of this research is to find out the effectiveness of Information Gap Activity in improving the students’ speaking ability. Since the purpose of this research is to find out the effectiveness of a technique, the researcher decided to conduct Pre – Experimental research with pre – test post – test model. The data were collected through speaking performance of pre – test and post – test. Then, they were analyzed by using formula of mean score, effect size, and t – test.The finding showed that the students’ speaking ability improved. Through the results of the calculations above, it can be concluded that Information Gap Activity is effective in improving the speaking ability of students of SMA Santo Paulus Pontianak in academic year 2013 / 2014. Keywords: Information Gap Activity, Speaking Ability